Lancar Membaca Permulaan Melalui Metode Scanning - -, Yuni Isnaeni (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This study aims to: (1) improve students' learning activities in the Indonesian language learning process using scanning techniques. (2) improve learning outcomes through speed reading. The research method uses quantitative descriptive through the analysis of learning outcomes activities collected through reading comprehension tests with scanning techniques. The subjects studied were students of class 1 MI P2A Meri totaling 30 students. Instruments used through tests or questions. The study was conducted in two cycles, the first cycle obtained data on the average score of learning activities 7.8 with good category. The second cycle an average score of 8.9 in the very good category. In the learning outcome activities also showed an increase, namely in the first cycle the comparison between students who had increased and decreased was 30% and 70%, meaning that there were still many students who did not understand the reading material in cycle one. After using the scanning method in the second cycle, there was an increase in student learning outcomes, namely 90% of students with increased results and 10% of students experiencing steady and decreasing results. Based on the data, this study shows that reading comprehension with scanning techniques is very appropriate to improve learning activities and student learning outcomes.